Autologous Fat Grafting for Treatment of Breast Implant Capsular Contracture: A Study in Pigs. (July 2014) - Roça, Guilherme Berto; Graf, Ruth; da Silva Freitas, Renato; Salles, Guataçara; Francisco, Julio Cesar; Noronha, Lucia; Maluf, Ivan
Background: Capsular contracture (CC) is a common complication after breast augmentation. Autologous fat grafting may be effective for restoring tissue vascularization and function. Objective: The authors evaluated the efficacy of autologous fat grafting in a porcine model as a treatment for CC after breast augmentation. Methods: This prospective study was performed in 20 female 30-day-old pigs. Each animal was implanted with three 30-cc textured silicone implants (stage 1 of the experiment). Group A served as the untreated control group. To induce CC, 2 mL of autologous fibrin glue was applied to the pericapsular space in group B and C animals at implantation. Three months after implantation (stage 2), the CCs of all groups were assessed by Baker classification and applanation tonometry (AT). Liposuction was performed in group B to harvest fat for these animals. Three months after group B underwent fat grafting, all 3 groups were reevaluated. Reassessments included Baker classification, AT, histologic analysis, and tensiometry (stage 3). Results: The deposition of mature and immature collagen was similar for the 3 groups. The amount of fat remaining around the implanted capsules did not differ significantly between the groups. At stage 3, group B exhibited significantly larger tonometry areas than did group C. The CCs in groups B and C were significantly thicker than those of group A, but the difference between groups B and C was not significant. Capsule rupture forces did not differ significantly between groups A and B but were significantly higher in group C compared with the other groups. Conclusions: Results in this animal model indicate that pericapsular lipoinjection may be a promising treatment for CC in humans.